Pengolahan Limbah Cair Depo Pemasaran Ikan Kabupaten Sidoarjo Menggunakan Tumbuhan Mansiang (Scirpus grossus) dengan Sistem Kontiyu Reaktor - Atik Widiyanti; Achmad Firdaus; Aulianitha Salsabella; Dinda Ayu Romadhotin Nazwa (Journal of Research and Technology, 2021)
Depo Pemasaran Ikan is the largest fish trading place in Sidoarjo Regency. It’s activities produce problems in the form of liquid waste originating from fish washing residue, fish washing waste that is brownish in color, cloudy and has a fishy smell, which has a very high content of organic matter and far so that it can pollute the environment. The purpose of this study was to determine the decrease in the degree of acidity (pH), Chemical Oxygen Demand (COD), and ammonium (NH4-N) in the waste using Scirpus grossus. The independent variable used was the variation in the number of plants (without plants, 5 plants and 10 plants). The waste used comes from the Fish Market Depot, Sidoarjo distric. The study began with the acclimatization process, then phytoremediation tests were carried out. Based on laboratory analysis, it was known that the best change in pH was obtained from a reactor with 10 plants, while the best COD and NH-4N were obtained from a reactor without plants.